THE EFFECT OF SOAKING DURATION AND CONCENTRATION OF BIDARA FRUIT EXTRACT ON COOKING LOSS, PH, AND ORGANOLEPTIC CHARACTERISTICS OF SPENT LAYER CHICKEN MEAT - T., Rahman; Wibawa, A.A.P.P.; Suranjaya, I G. (Jurnal Peternakan Tropika, 2024)
This study aimed to investigate the influence of soaking duration and concentration of bidara fruit extract on cooking loss, pH, and organoleptic characteristics (aroma, taste, tenderness) of spent layer chicken meat. The research was conducted at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University on June 20, 2022. A completely randomized design (CRD) with a factorial pattern was employed, consisting of two factors: soaking duration (L1: 1 hour, L3: 3 hours) and concentration of bidara fruit extract (K1: 25%, K2: 50%). Each treatment combination was repeated four times. The observed variables included cooking loss, pH, and organoleptic characteristics. The analysis results indicated that there was no significant interaction between soaking duration and concentration of bidara fruit extract (P>0.05) regarding cooking loss, pH, and organoleptic characteristics. However, soaking duration exhibited a significant effect on the tenderness value of spent layer chicken meat (P<0.05). Regarding the concentration factor, an increase in cooking loss was observed in spent layer chicken meat. Based on the research findings, it can be concluded that there was no significant interaction between the concentration and soaking duration factors on cooking loss, pH, and organoleptic characteristics (aroma, taste, tenderness). The favorable result obtained was that longer soaking duration improved the tenderness value, indicating that the longer the soaking duration, the higher the tenderness value.